Alien ocean animals - Colosi, Rosie; National Geographic Society (U.S.) (Washington, DC : National Geographic Kids, 2020)
Journey through the depths of the ocean into the dark Midnight Zone and discover the mysterious animals that live there. Learn about how their bodies make their own light or adapt to living in low-light areas, how they hunt, what they eat, and how they keepthemselves safe from predators. --Publisher.
Out of this world -- Enter the midnight zone -- Light in the darkness -- Open wide! -- Staying safe -- 6 cool facts about ocean exploration -- Hidden away -- Eyes of the deep -- Underwater party animals -- A lot more to explore! -- Quiz whiz.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Age 4-6.
K to Grade 3.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Marine animals -- Juvenile literature; Deep-sea animals -- Juvenile literature; Deep-sea animals; Marine animals; Electronic books- OSLIS; Informational works; Juvenile works; Informational works; Documents d'information.